Ultrasonic Waves Regulate Antioxidant Defense and Gluconeogenesis to Improve Germination From Naturally Aged Soybean Seeds - Yutao Huang; Gaofu Mei; Xujun Fu; Yang Wang; Xiaoli Ruan; Dongdong Cao (Frontiers in Plant Science, 2022)
Soybean seeds contain substantial triacylglycerols and fatty acids that are prone to oxidation during storage, contributing to the dramatic deterioration of seed vigor. This study reports an ultrasonic waves treatment (UWT), which is a physical method capable of promoting the germination ability of the aged soybean seeds by regulating the antioxidant defense and gluconeogenesis. Germination test revealed that UWT significantly increased the germination rate and seedlings’ establishment of the soybean seeds stored for 12 months, although insignificantly impacting the vigor of fresh (stored for 1 month) and short-term stored (for 6 months) seeds. Further biochemical analysis revealed that UWT decreased the hydrogen peroxide (H2O2), O2⋅–, and malondialdehyde contents in the aged soybean seeds during early germination. Consistently, UWT prominently elevated the activities of superoxide dismutase, catalase, and acetaldehyde dehydrogenase, and also the corresponding gene expressions. Besides, the soluble sugar content of UWT was significantly higher than that of the untreated aged seeds. Analysis of enzyme activity showed UWT significantly upregulated the activities of several key enzymes in gluconeogenesis and the transcription levels of corresponding genes. Moreover, UWT enhanced the invertase activity within aged seeds, which was responsible for catalyzing sucrose hydrolysis for forming glucose and fructose. In summary, UWT improved germination and seedlings establishment of aged soybean seeds by regulating antioxidant defense and gluconeogenesis. This study expands the application of ultrasonication in agricultural production and further clarifies the physiological and molecular mechanisms of the aged seed germination, aiming to provide theoretical and practical guidance for seed quality and safety.